Answer: The required solution of the given system is
(x, y) = (3, 1) and (4, 0).
Step-by-step explanation: We are given to solve the following system of equations :
![x+y=4~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\y=x^2-8x+16~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)](https://img.qammunity.org/2020/formulas/mathematics/college/klyg4qh38tov3hm53fwd7zvdel19aleftc.png)
From equation (i), we have
![x+y=4\\\\\Rightarrow y=4-x~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(iii)](https://img.qammunity.org/2020/formulas/mathematics/college/2sben9ghky17px0wjz5gsib4cde3rc621i.png)
Substituting the value of y from equation (iii) in equation (ii), we get
![y=x^2-8x+16\\\\\Rightarrow 4-x=x^2-8x+16\\\\\Rightarrow x^2-8x+16-4+x=0\\\\\Rightarrow x^2-7x+12=0\\\\\Rightarrow x^2-4x-3x+12=0\\\\\Rightarrow x(x-4)-3(x-4)=0\\\\\Rightarrow (x-3)(x-4)=0\\\\\Rightarrow x-3=0,~~~~~~~x-4=0\\\\\Rightarrow x=3,~4.](https://img.qammunity.org/2020/formulas/mathematics/college/stvc8b76pm89eoei7wmbjsak0bd05g2rip.png)
When, x = 3, then from (iii), we get
![y=4-3=1.](https://img.qammunity.org/2020/formulas/mathematics/college/7mtulrciy8gfbykcu0lxar430blp2tgv48.png)
And, when x = 4, then from (iii), we get
![y=4-4=0.](https://img.qammunity.org/2020/formulas/mathematics/college/dg4uk4pen7sfkwdnoivmjmc3n9i0l0e7rd.png)
Thus, the required solution of the given system is
(x, y) = (3, 1) and (4, 0).